Shattered Visage : The Real Face of IVF ,Surrogacy and Modified Babies in Pinki Virani’s Book Politics of the Womb - Aruna , G.; Sambaiah, M (International Journal of Psychosocial Rehabilitation, 2020)
Since procreation is the mainstay of humanity , it has been one of the most discussed themes across the world literature, myths and history. It was also treated by the male society as the only way to prove their manliness, propagating genealogy and prestige. Preserving the tradition and legacy through the so called „heir‟ considered to be the greatest achievement from times immemorial. But, in the age of scientific advancement and information explosion, even in 21 century, the attempts of coercive or artificial birthing and fertility is still frantically rampant and becoming detrimental to the human race especially to the very women species. The paper focuses how Pinki Virani in her investigative and thought provoking book Politics of the Womb: The Perils of Surrogacy, IVF, Surrogacy & Modified Babies(2017) throws light upon the greedy and commercial reproduction industry and examines not only its rates of success and failure, but also the long-term effects of the procedures on mother and child. For her, it‟s a business of baby- making. She proves, through the artificial process, how the human element is sacrificed and uses and reuses women. Writing the first book of its kind anywhere in the world, the author gathers various proofs from global experts shows how the business mafia by business interest of a burgeoning repro tech industry causes fatal damages to humanity in general and women in specific. This paper meticulously explores the author‟s concern for women and provides urgent message to prospective parents, young women, and men to take a long, hard look at artificial reproduction so as to be seduced by its seemingly miraculous medico-technology.